Early inflammatory events of mastitis—a pilot study with the isolated perfused bovine udder - Kathrin Susanne Brand (BMC, 2021)
Abstract Background Bovine mastitis is an important health and cost factor in the milk industry. To elucidate whether isolated perfused bovine udders can be used to study early inflammatory events of mastitis, 1 mg of lipopolysaccharide (LPS) was instilled into quarters of 10 isolated perfused bovine udders. Three hours and 6 h after LPS instillation, tissue samples were taken from the gland cistern and base of the udder, subsequently stored in RNAlater and processed for the determination of inflammation-dependent gene regulation by real-time RT-qPCR. Gene expression analysis was performed using delta-delta Ct method. To translate mRNA results to protein, IL-1ß and IL-6 were determined in tissue homogenate by ELISA. Results The instillation of 1 mg LPS lead to an increased expression of pro-inflammatory cytokines and chemokines like TNF-α, CCL20, CXCL8 as well as of IL-1 ß, IL-6 and IL-10, lingual antimicrobial peptide (LAP) and S100A9. However, the degree of elevation differed slightly between gland cistern and udder base and markedly between 3 and 6 h after instillation, with a distinct increase in mediator expression after 6 h. IL-1β protein increased in a time-dependent manner, whereas IL-6 was unchanged within 6 h of LPS instillation. Conclusion Compared to in vivo studies with instillation of LPS into udders of living cows, a similar inflammation-dependent gene regulation profile can be mimicked in the isolated perfused bovine udder, indicating a supplementation of animal experiments. Graphical abstract